Herbal based nanoparticles as a possible and potential treatment of cancer: a review - Roshan Yadav; Himmat Singh Chawra; Gaurav Dubey; Md Sabir Alam; Vikram Kumar; Pragya Sharma; Navneet Kumar Upadhayay; Tejpal Yadav (Exploration of Targeted Anti-tumor Therapy)
Cancer is the greatest cause of mortality worldwide. Various drug classes treat various cancers. Nanoformulations made from natural sources are being studied for treating several diseases, including cancer. Surgery, chemotherapy, immunotherapy, and radiation have mostly failed to treat cancer. These drugs may damage quickly dividing healthy tissues, structural anomalies, bodily toxicity, long-term side effects, tumor cell drug resistance, and psychiatric disturbances. Researchers are developing nanoscale medicines using natural medications like Malva sylvestris and Curcumin to lower concentrations and improve target specificity. Nanoparticles’ small size and unique properties make them beneficial. They encapsulate medicinal ingredients, improving solubility, medication release, cellular absorption, and delivery. Nanoparticles may better identify and bind to cancer cells when functionalized with ligands. Natural chemicals and nanotechnology may improve medication availability, distribution, and targeting to cancer cells, making cancer treatments more effective and safe. Nanomedicine, which employs nanoparticles to treat cancer and malignant cells, has grown rapidly because nanodrugs are more effective and have fewer side effects than current commercial cancer drugs. Nanotechnology-based natural chemicals and pharmaceutical delivery methods for cancer therapy are covered in this review article. The paper discusses nanoparticle pros and cons and natural chemicals’ cancer-fighting appeal.